1 Introduction: Inalienability, Value, and the Construction of Social Difference. Issue 1 (March 2013) - Kovacevich, Brigitte; Callaghan, Michael G.; Kovacevich, Brigitte; Callaghan, Michael G.
ABSTRACT Annette Weiner's concept of "inalienable wealth" is a powerful theoretical construct that can help archaeologists understand how artifacts gained value, were used to foster group identity, and created social difference. In this chapter we first review the concept of inalienable wealth as conceptualized by Weiner for use in understanding cultural practices of contemporary societies in Melanesia. We then discuss why inalienable wealth holds potential for archaeological datasets, how archaeologists have used it in the recent past, and how contributors to this volume employ the concept.